From Directed Lending To Green Taxonomy: Sustainable Finance Adoption In Nepal’s Commercial Banking Sector - Beni Shah Shrestha, (Journal of Contemporary Review, 2025)
Amid escalating environmental challenges, green finance has emerged as a critical mechanism for aligning economic growth with sustainability, particularly in developing nations like Nepal. This study comprehensively investigates the green finance practices adopted by Nepalese commercial banks, evaluating their alignment with regulatory frameworks such as the Nepal Rastra Bank’s (NRB) Environmental and Social Risk Management (ESRM) Guidelines and the Nepal Green Finance Taxonomy. Employing a mixed-methods approach by integrating an extensive literature review, analysis of secondary data from NRB and bank reports, and in-depth interviews with banking professionals from diverse institution, the research identifies key practices, including green lending for renewable energy, sustainable agriculture, and waste management. It also uncovers persistent barriers, such as limited technical expertise, regulatory inconsistencies, and heightened risk perceptions. Findings reveal that while innovative initiatives, such as green bond issuances, are gaining traction, adoption remains largely compliance-driven rather than strategically embedded. These practices contribute to modest improvements in financial performance, stakeholder trust, and environmental outcomes, yet broader systemic reforms are essential. By providing a detailed analysis, this study enriches the sparse literature on sustainable finance in South Asia, offering actionable recommendations for policymakers, regulators, and banks to amplify green investments in support of Nepal’s Sustainable Development Goals (SDGs).